Cognitive Impairment and Affective Disorders in Patients With Obstructive Sleep Apnea Syndrome - Bilyukov, Radoslav G.; Nikolov, Martin S.; Pencheva, Ventsislava P.; Petrova, Daniela S.; Georgiev, Ognian B.; Mondeshki, Tsanko L.; Milanova, Vihra K. (Frontiers in Psychiatry, 2018)
Sleep-related breathing disorders could be accompanied by or caused by a variety of medical conditions. They are considered to be a significant medical and social problem. Together with excessive daytime sleepiness, patients with obstructive sleep apnea experience neuropsychological symptoms such as anxiety, attention deficits, cognitive impairment, depressive symptoms and other psychological disturbances leading to social adjustment difficulties. Patients diagnosed with obstructive sleep apnea demonstrate a decline in a wide spectrum of cognitive abilities, including memory, attention, psychomotor speed, executive, verbal and visual-spatial skills. The aim of this study is to investigate the cognitive functioning and affective disorders among patients with obstructive sleep apnea syndrome and to examine the frequency and severity of cases in comparison with a control group consisting of healthy volunteers. Our research has shown that there is a relation between sleep apnea and cognitive impairments and affective changes. This relation can be explained by the direct effect of the syndrome on the patient, where the main connecting factor is the severity and the distribution of excessive daytime sleepiness. Along with treatment of the somatic medical condition, it is extremely important that the patient’s mental state is treated as well.